Angiotensin-Neprilysin Inhibition and Renal Outcomes in Heart Failure With Preserved Ejection Fraction. Issue 13 (29th September 2020) - Mc Causland, Finnian R.; Lefkowitz, Martin P.; Claggett, Brian; Anavekar, Nagesh S.; Senni, Michele; Gori, Mauro; Jhund, Pardeep S.; McGrath, Martina M.; Packer, Milton; Shi, Victor; Van Veldhuisen, Dirk J.; Zannad, Faiez; et al.
Abstract : Background: In patients with heart failure, chronic kidney disease is common and associated with a higher risk of renal events than in patients without chronic kidney disease. We assessed the renal effects of angiotensin/neprilysin inhibition in patients who have heart failure with preserved ejection fraction enrolled in the PARAGON-HF trial (Prospective Comparison of ARNI With ARB Global Outcomes in HF With Preserved Ejection Fraction). Methods: In this randomized, double-blind, event-driven trial, we assigned 4822 patients who had heart failure with preserved ejection fraction to receive sacubitril/valsartan (n=2419) or valsartan (n=2403). Herein, we present the results of the prespecified renal composite outcome (time to first occurrence of either: ≥50% reduction in estimated glomerular filtration rate (eGFR), end-stage renal disease, or death from renal causes), the individual components of this composite, and the influence of therapy on eGFR slope. Results: At randomization, eGFR was 63±19 mL·min –1 ·1.73 m – 2. At study closure, the composite renal outcome occurred in 33 patients (1.4%) assigned to sacubitril/valsartan and 64 patients (2.7%) assigned to valsartan (hazard ratio, 0.50 [95% CI, 0.33–0.77]; P =0.001). The treatment effect on the composite renal end point did not differ according to the baseline eGFR (<60 versus ≥60 mL·min –1 ·1.73 m –2 ( P -interaction=0.92). The decline in eGFR was less for sacubitril/valsartan than for valsartan (–2.0 [95% CI, –2.2 to –1.9] versus –2.7 [95% CI, –2.8 to –2.5] mL·min –1 ·1.73 m –2 per year). Conclusions: In patients with heart failure with preserved ejection fraction, sacubitril/valsartan reduced the risk of renal events, and slowed decline in eGFR, in comparison with valsartan. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01920711. Abstract : Supplemental Digital Content is available in the text.